2020
DOI: 10.1002/jbm.a.36895
|View full text |Cite
|
Sign up to set email alerts
|

A laminin‐211‐derived bioactive peptide promotes the osseointegration of a sandblasted, large‐grit, acid‐etched titanium implant

Abstract: Early implant loading is very important for reducing the duration of missing teeth in human patients. The laminin‐derived peptide, DLTIDDSYWYRI motif (Ln2‐P3), accelerates bone healing. Therefore, to investigate the hypothesis that Ln2‐P3 increases the bone response to sandblasted, large‐grit, acid‐etched (SLA) titanium implants, the effect of the Ln2‐P3 peptide on the osseointegration of SLA titanium implants was evaluated in vitro and in vivo. Human osteoblast‐like cells were cultured on untreated, scrambled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 31 publications
1
14
0
Order By: Relevance
“…Yu et al [131] applied picosecond laser ablation to modify Ti substrate and demonstrated that the resultant surface of Ti with micro-groves promoted cell adhesion. The subtractive modifications of biomaterial surface may also be applied to prepare the surface before the coating process (Figure 4) [132][133][134][135][136][137][138][139]. By increasing the roughness of the surface, better adhesive bond between the coating and the surface of modified material may be achieved [140].…”
Section: Subtractive Modifications Of Biomaterials Surfacementioning
confidence: 99%
“…Yu et al [131] applied picosecond laser ablation to modify Ti substrate and demonstrated that the resultant surface of Ti with micro-groves promoted cell adhesion. The subtractive modifications of biomaterial surface may also be applied to prepare the surface before the coating process (Figure 4) [132][133][134][135][136][137][138][139]. By increasing the roughness of the surface, better adhesive bond between the coating and the surface of modified material may be achieved [140].…”
Section: Subtractive Modifications Of Biomaterials Surfacementioning
confidence: 99%
“…In the current study, hafnium coating appears to have offered similar biocompatibility (aspartate transaminase (AST), alanine aminotransferase (ALT), and creatine kinase (CK) enzyme assay), statistically significant improvement (independent Student's t-test, p < 0:05) in insertion torque (25:42 ± 3:96) and removal torque (29:17 ± 2:88) than commercially pure titanium with insertion torque (22:08 ± :57) and removal torque (25:42 ± 2:57). Hafnium has proved to have good tissue response and osseointegration, along with required mechanical properties [39][40][41][42][43][44][45][46][47][48]. Though these results seem to favour hafnium, it is necessary to analyse the factors that could have confounded our study.…”
Section: Discussionmentioning
confidence: 99%
“…In 1984, Marcel Pourbaix proposed hafnium as a metal to be considered for surgical implants due to the passive state of the metal with properties like high ductility, strength, resistance to corrosion, and mechanical damage. Various in vitro studies were conducted on hafnium metal [33][34][35][36][37][38][39][40][41][42].…”
Section: Introductionmentioning
confidence: 99%
“…More recently, Choi et al studied the influence on osseointegration of an active, laminin-derived peptide (Ln2-P3) in a rabbit tibia model [ 49 ]. Laminin is an ECM protein mainly involved in the mechanism of adhesion and proliferation of basal lamina cells [ 51 ].…”
Section: Biomolecules Used In In Vivo Studiesmentioning
confidence: 99%